Kajian Potensi Medan Magnet Extremely Low Frequency (ELF) Untuk Terapi Osteoporosis - Lisa Listyo Wati; Cindy Ferdianty; Sudarti . (Peneliti.net, 2023)
This research was conducted to determine the potential of the ELF magnetic field for Osteoporosis therapy. This type of research design used is descriptive research. The research method used is Article Review by reviewing 30 articles from 2007 to 2023 originating from international articles and national articles. The results showed that the intensity of magnetic field exposure with the right intensity will have a good effect on cell proliferation, osteoblast formation and healing of osteoporosis, but the intensity given is not right will have an impact on damage to other organs of the body. Based on the analysis that has been carried out on 30 articles, both national and international articles, it is concluded that the use of the right magnetic field intensity can help treat osteoporosis. However, exposure to Extremely Low Frequency (ELF) Electromagnetic Fields still has a negative impact on health if the intensity of the exposure does not match its use.